Distúrbios psíquicos menores em agentes socioeducadores dos centros de atendimento socioeducativo do Rio Grande do Sul - Greco, Patricia Bitencourt Toscani (2011)
The work of agents in the socio Socio-Educational Service Centers is ruled by a high concentration, fast pace, unpredictability, great responsibilities; which can lead to constant stress. Based on the guiding question: there is an association between high psychological demands at work, low worker control over work activities and development of minor psychiatric disorders (MSD) on these agents?, This study aimed to investigate the psychosocial dimensions - control and psychological demands of work and its association with the occurrence of MPD agents of socioeducational workers of CASE/RS. The central hypothesis is that the association is positive. It is a cross-sectional study with a sample of 381 socio agents. In order to evaluate MPD and groups of the Karasek demand-control model, the Brazilian versions of the Self Report Questionnaire-SRQ-20 and Job Stress Scale - JSS were respectively applied. Data collection was performed using self-administered questionnaire in the period from March to August 2011. Data insertion was conducted using Epi-Info ®, version 6.4, with double independent typing. After checking for errors and inconsistencies, the data analysis was performed in PASW® (Predictive Analytics Software) 18.0 for Windows. To examine associations, chi-square test has been applied, Odds Ratio and its respective confidence intervals (CI 95%). Sociodemographic, employment, health habits were tested and those associated (p<0.25) both the exposure and the outcome (satisfaction with the workplace, number of agents on the scale, shift, day off work, suspicion for alcoholism, leisure time, physical and psychological activity) were tested in the multivariate models. As a result, it was found that 19.2% of socioeducational agents are in the quadrant high demand. The overall prevalence of suspicion for MPD was 50.1%. After adjusting for potential confounders, the odds of mental disorders was higher in active work quadrant (OR = 1.99, CI 95%=1.09 - 3.63), followed by high demand quadrant (OR = 2.05, IC95% = 1.03 - 4.09) compared to the agents of low demand quadrant. When the dimensions psychological demands and control are evaluated individually, both were associated with MPD. These results indicate high psychological demand, which has negative health effects of these workers, even when job control is high. In this sense, it is necessary to consider the issues of work organization in the institution, besides the planning of actions to promote health, prevent mental illness of the socio agents.